Resiliensi akademik siswa - Rizka Irawan; Dian Renata; Sabrina Dachmiati (Universitas Indraprasta PGRI, 2022)
academic resilience is one component of self that needs to be owned by every student in the face of academic pressure. Uniquely, not all students have optimal academic resilience. This study aims to determine the description of students' academic resilience. This research is a descriptive quantitative research. The population in this study was 204 students. Samples were drawn randomly by determining the magnitude using the Slovin formula at a significance level of 0.05. Through this formula, the number of samples was 135 students. Data were collected through a questionnaire technique and analyzed using descriptive analysis. The results showed that the students' academic resilience was in the medium category. For this reason, efforts are needed from teachers, specifically Guidance and Counseling teachers in improving students' academic resilience.